Sympathetic Hyperactivity and Age Affect Segregation and Expression of Neurotransmitters - Merino-Jiménez, Candelaria; Miguel, Filiberto; Feria Pliego, Jessica Abigail; Zetina Rosales, María Elena; Cifuentes, Fredy; Morales, Miguel Angel (Frontiers in Cellular Neuroscience, 2018)
Sympathetic neurons of the rat superior cervical ganglion (SCG) can segregate their neurotransmitters and co-transmitters to separate varicosities of single axons. We have shown that transmitter segregation is a plastic phenomenon and that it is correlated with the strength of synaptic transmission. Here we determined whether sympathetic dysfunction occurring in stress and hypertension was correlated with plastic changes of neurotransmitter segregation. We characterized the expression of the markers, L-glutamic acid decarboxylase of 67 kDa (GAD67) and vesicular acetylcholine transporter (VAChT) in the SCG of cold stressed and spontaneously hypertensive rats (SHR). Considering that the SCG comprises a heterogeneous neuronal population, we explored whether the expression and segregation of neurotransmitters would also have an intraganglionic heterogeneous distribution in ganglia of stressed and hypertensive rats. Furthermore, since hypertension in SHR is detected around 8-10 weeks, we evaluated expression and segregation of ACh and GABA in adult hypertensive (12-week old) and young pre-hypertensive (6-week old) SHR. We found an increase in segregation of ACh and GABA with no change in transmitter expression in ganglia of stressed animals. In contrast, in SHR, there was an increase in GABA expression, although segregation did not vary. Segregation showed a caudo-rostral gradient in controls but not in the ganglia of stressed animals. GABA expression showed a rostro-caudal gradient in adult SHR, which was not present in young 6-week old rats. In young SHR, ACh increased and, unexpectedly, segregation of ACh and GABA was higher than in adults. Data suggest that ACh and GABA segregation increases in acute sympathetic hyperactivity like stress, but does not vary in chronic hyperactivity such as in hypertension. Changes in segregation are age-dependent and might be involved in the mechanisms underlying stress and hypertension.